Cheilolejeunea amazonica (Lejeuneaceae, Marchantiophyta), a new tepui species from northern Brazil - Bastos, Cid José Passos; Zartman, Charles E. (Phytotaxa, 2016)
Cheilolejeunea amazonica, a new species currently known only from one outlying sandstone tepui of the Guiana Highlands in northern Brazil, Serra Aracá, is described and illustrated. This new taxon is phenotypically aligned with Cheilolejeunea Sect. Strepsilejeunea due to its sharply pointed leaf apex. Locally, the plant is abundant growing in large mats on vertical sandstone seeps along streams draining the northeastern flanks of this tepui.